Shooting Practice Model in Hockey Games Room - Nur Fauziah; Taufik Rihatno; Aan Wasan; Oman Unju Subandi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to produce innovative training training models for room hockey players that can provide benefits to athletes and room hockey coaches to convey varied training models and can understand and achieve the expected training results in order to play room hockey well. The method used in this research is the research and development method. The subjects in this study were UNJ hockey club athletes as small group trial subjects and Tangerang City hockey club athletes as large group trial subjects. The pre-test is carried out after conducting small group revisions and product trials. This pre-test is carried out before the research subjects are given treatment. After being treated with 16 models, variations of training models and models were evaluated, namely post-tests were carried out on 35 hockey athletes to find out whether there was an increase in accuracy. The pre-test data conducted before treatment was 16.28 After the test was carried out it was found that the accuracy of players increased, marked by increasing the post-test average of 24.14. This means that the exercise variation model has improved. So the conclusion is that there is a significant relationship.